Upaya Pencegahan Stunting di Masa Pandemi Covid-19 Melalui Edukasi 2P (Pemenuhan Gizi Seimbang dan Pemberian Madu) - Hapzah Hapzah; Yudianti Yudianti; Rahmat Haji Saeni; Nurbaya Nurbaya (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2022)
Based on the data of SSGI 2021, the prevalence of stunting among under-five children in West Sulawesi is still quite high, namely 40.38%. Disturbances in the food and health systems caused by the Covid-19 pandemic have the potential to further exacerbate nutritional problems among children. One form of social support to the community is to maximize family resources through increasing knowledge related to preventing stunting problems during the Covid-19 pandemic. This community service activity aimed to provide 2P education, namely the provision of balanced nutrition and the Provision of honey. Educational materials are provided in the form of video slides sent via WhatsApp Group. The main targets were 15 participants that consist of cadres and mothers of under five children in the working area of ​​the Tinambung Health Center. Evaluation was carried out in the form of questions and answers and discussions with participants. Health workers need to be more innovative in promoting health and nutrition during the pandemic, such as regularly spreading nutrition messages through WhatsApp messages. ABSTRAK Berdasarkan hasil SSGI 2021 menunjukkan bahwa prevalensi balita stunting di Sulawesi Barat masih cukup tinggi yaitu 33,8%. Gangguan pada sistem pangan dan kesehatan yang diakibatkan oleh pandemi Covid-19 berpotensi semakin memperburuk masalah gizi balita. Salah satu bentuk dukungan sosial kepada masyarakat adalah dengan memaksimalkan sumber daya keluarga melalui peningkatan pengetahuan terkait pencegahan masalah stunting di masa pandemi Covid-19. Kegiatan pengabdian masyarakat ini bertujuan memberikan edukasi 2P yaitu pemenuhan gizi seimbang dan pemberian madu. Materi edukasi diberikan dalam bentuk video slides melalui WhatsApp Group. Sasaran utama kegiatan ini adalah 15 peserta yang terdiri dari kader dan ibu balita yang ada di wilayah kerja Puskesmas Tinambung. Evaluasi dilakukan dalam bentuk tanya jawab dan diskusi dengan peserta. Petugas kesehatan perlu lebih inovatif dalam melakukan promosi kesehatan dan gizi selama masa pandemi seperti rutin menyebarkan pesan gizi melalui pesan WhatsApp.